2003
DOI: 10.1002/dmrr.407
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses and type 1 diabetes

Abstract: The development of type 1 diabetes mellitus (T1DM) has been linked to exposure to environmental triggers, with Enteroviruses (EV) historically considered the prime suspects. Early serological studies suggested a link between EV infections and the development of T1DM and, though controversial, have been bolstered by more recent studies using more sensitive techniques such as direct detection of the EV genome by RT-PCR in peripheral blood. In this review, we consider the weight of evidence that EV can be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 101 publications
(116 reference statements)
1
32
0
Order By: Relevance
“…Interestingly, cross-reactivity was only detected in animals immunized with enteroviruses belonging to group B, in which a 6 amino acid homology between human GAD 65 and the non-structural enteroviral protein (P2C) has been reported [4,8,9]. Accordingly, homology between these two proteins could explain the cross-reaction observed in our study.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Interestingly, cross-reactivity was only detected in animals immunized with enteroviruses belonging to group B, in which a 6 amino acid homology between human GAD 65 and the non-structural enteroviral protein (P2C) has been reported [4,8,9]. Accordingly, homology between these two proteins could explain the cross-reaction observed in our study.…”
supporting
confidence: 49%
“…Molecular mimicry is one of the hypotheses that have been elaborated to explain associations between enteroviruses and autoimmunity. This phenomenon describes a situation in which primary or tridimensional structural similarities between viral proteins and autoantigen determinants can lead to functional T and B cell cross-reactivity resulting in tissue damage and perpetuation of the autoimmune response [4].…”
mentioning
confidence: 99%
“…Rubella virus (Karvonen et al, 1993), mumps virus (Hyoty et al, 1988, cytomegalovirus (Ward et a., 1979), rotavirus (Honeyman et al, 2000) and enteroviruses (EV) (Lonnrot et al, 2000;Stene et al, 2010) have all been suggested as environmental factors contributing to type 1 diabetes. EV, especially those of the Coxsackievirus B (CVB) group (Hyöty et al, 1988;Varela-Calvino & Peakman , 2003;Green et al, 2004), are historically the prime suspects as important aetiological determinants and seroepidemiological, histopathological, animal studies, and in vitro experiments have provided the strongest overall evidence for these viruses. The EV genus of the Picornaviridae family is a large group of human pathogens traditionally divided into polioviruses, coxsackieviruses, echoviruses and the new EV, and each group contains a range of serotypes (King et al, 2000;Roivainen, 2006).…”
Section: Enteroviruses and Type 1 Diabetesmentioning
confidence: 99%
“…In the cardiac context, injury is caused by a direct cytopathic effect of the virus, an immune response to viral infection or autoimmunity triggered by the viral infection (Huber, 2006). Several mechanisms, including molecular mimicry, bystander activation of autoreactive T cells, superantigenic activity of viral proteins, viral infection and persistence, not mutually exclusive, have been proposed to explain the relationship between EV infections and induction of autoimmune diseases (extensively reviewed in Varela-Calvino & Peakman, 2003;Ercolini & Miller, 2009). As for a role in type 1 diabetes, results have been somewhat conflicting and not conclusive (von Herrath, 2009;Tauriainen et al, 2010).…”
Section: Enteroviruses and Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation